Follicular Fluid from Infertile Women with Mild Endometriosis Impairs In Vitro Bovine Embryo Development: Potential Role of Oxidative Stress - Vanessa Silvestre Innocenti Giorgi; Rui Alberto Ferriani; Paula Andrea Navarro (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective To investigate whether follicular fluid (FF) from infertile women with mild endometriosis (ME) alters in vitro bovine embryo development, and whether the antioxidants N-acetyl-cysteine (NAC) and/or L-carnitine (LC) could prevent such damages. Methods Follicular fluid was obtained from infertile women (11 with ME and 11 control). Bovine oocytes were matured in vitro divided in: No-FF, with 1% of FF from control women (CFF) or ME women (MEFF); with 1.5mM NAC (CFF + NAC, MEFF + NAC), with 0.6mg/mL LC (CFF + LC, MEFF + LC), or both antioxidants (CFF + NAC + LC, MEFF + NAC + LC). After in vitro fertilization, in vitro embryo culture was performed for 9 days. Results A total of 883 presumptive zygotes were cultured in vitro. No differences were observed in cleavage rate (p = 0.5376) and blastocyst formation rate (p = 0.4249). However, the MEFF group (12.5%) had lower hatching rate than the No-FF (42.1%, p = 0.029) and CFF (42.9%, p = 0.036) groups. Addition of antioxidants in the group with CFF did not alter hatching rate (p ≥ 0.56), and in groups with MEFF, just NAC increased the hatching rate [(MEFF: 12.5% versus MEFF + NAC: 44.4% (p = 0.02); vs MEFF + LC: 18.8% (p = 0.79); versus MEFF + NAC + LC: 30.8% (p = 0.22)]. Conclusion Therefore, FF from infertile women with ME added to medium of in vitro maturation of bovine oocytes impairs hatching rate, and NAC prevented these damages, suggesting involvement of oxidative stress in worst of oocyte and embryo quality of women with ME.